Modified Glasgow Prognostic Score, Prognostic Nutritional Index and ECOG Performance Score Predicts Survival Better than Sarcopenia, Cachexia and Some Inflammatory Indices in Metastatic Gastric Cancer - DANE, FAYSAL; YUMUK, PERRAN FULDEN; AKIN TELLİ, TUĞBA (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2021)
Background: Gastric carcinoma (GC) patients usually present with locally advanced or metastatic disease; therefore treatment aim is mainly palliation. In this study our purpose is to analyze the prognostic values of the sarcopenia index (SI), cachexia index (CIn) and other inflammatory indexes (advanced lung cancer inflammation index [ALI], modified Glasgow Prognostic Score [mGPS], prognostic index [PI], prognostic nutritional index [PNI] and neutrophil-to-lymphocyte ratio [NLR]) in metastatic GC patients. Methods: Data from the files of metastatic GC patients, who applied to Medical Oncology outpatient clinic in Marmara University Pendik Education and Research Hospital between January 2011 and June 2016, were retrospectively reviewed. Five hundred seventy patients with gastric cancer were detected. Exclusion criteria were the inability to reach the patient surveys for prognostic index calculations, the presence of additional comorbidities to affect the laboratory parameters, and the absence of metastatic disease. Finally, 87 of these patients were included in this study. For SI calculation L3 level muscle area was measured from patients' computed tomography (CT) by a radiologist. SI reference value was obtained from western-EGWSOP (The European Working Group on Sarcopenia in Older People) and eastern (Harada Y, et al.) sources separately, as Turkey doesn't have a reference value for SI. NLR cutoff value was accepted as the median value of patients' NLR measurements. Statistical analysis was conducted using SPSS. Kaplan-Meier and Cox regression models were used to assess independent prognostic factors. The area under the curve was used to compare the prognostic value of indexes. Results: The median length of follow-up of 87 patients was nine months (1-64 mo,/s), and 78 patients died during follow-up. Fifty-nine patients were male (63%), and the median age was 62 (range, 23-88). According to univariate analysis high mGPS and PI score, PNI level <45, NLR level >= 3.41, ALI level <18, CI level under 35, SI (Harada Y, et al) <= 44.5 for males and <= 36.5 for females, ECOG score >= 2, weight loss more than 10% during last 6 mo, BMI under 24 were poor prognostic factors. Age, gender, having multiple organ metastasis, history of gastric surgery, positivity C-erb-B2, SI (EGWSOP) <= 52.4 for males, and <= 38.4 for females did not have any impact on survival. According to multivariate analysis, high mGPS (score 2) (HR 2,494, 95% CI 1.25-4 .94, p = 0.02), PNI (score 1) (HR 4.2, 95% CI 1.73-10.1, p < 0.001) and ECOG score (>= 2) (HR 1.541, 95% CI 1,089-4,214, p = 0.004) have been found to be independent prognostic factors which are determining the survival. mGPS was found to be more valuable than other indexes for predicting mortality by measuring the AUC with ROC analysis. Conclusions: In our study, mGPS, PNI and ECOG score were independent indicators for shorter survival in metastatic gastric cancer patients. mGPS and PNI, which can be done by using only serum CRP, albumin level and complete blood count, might be inexpensive, practical and beneficial to use in routine clinical practice to determine survival.
Keywords: LYMPHOCYTE RATIO; LUNG-CANCER; CURATIVE RESECTION; BODY-COMPOSITION; NEUTROPHIL; CHEMOTHERAPY; OUTCOMES; OBESITY